Open Source Policies and Processes For In-Bound Software (Journal of Open Law, Technology & Society, 2010)
Virtually all companies use some amount of software that has been made available to the company under an open source license. The re-use of these valuable software components is inevitable and should not be discouraged. In addition to reducing the time and cost of development, re-use of components that have withstood the tests of time and the many eyeballs of critical peer review provides assurance of quality and reliability. As companies begin to recognize the enormous value of this software, they come to the realization that they must implement policies and systematic processes that assure compliance with the terms of open source licenses. This includes both managing the use of open source software within the company and external obligations arising under relationships with open source communities. This article focuses on policies relating to in-bound code.